Keterampilan Guru Mengadakan Variasi Pembelajaran Matematika Pada Materi Bola - Pomalato, Sarson W.Dj.; Oroh, Franky A.; Munawir, Arief; Wali, Lazna Suci (Research in the Mathematical and Natural Sciences, 2024)
This study aims to describe the skills of teachers in implementing variations in the teaching of curved surface solid geometry. The discussion of the curved surface solid focuses on the topic of spheres with the students of SMP Negeri 1 Paguyaman as the research subjects. Research data was obtained through observation of the teaching process and questionnaires. This study employed a descriptive research method to describe the use of variations in mathematics teaching. The study was conducted in class IX of SMP Negeri 1 Paguyaman. The research subjects were 27 ninth-grade SMP Negeri 1 Paguyaman students, consisting of 17 female and 10 male students. Data analysis was performed using quantitative descriptive analysis techniques. The results show that the use of variations in the teaching of mathematics on curved surface solids of spheres reached the "very good" category, with indicators: teacher’s ability to implement variations in teaching at 84%, student activity during the lessons at 84%, and positive student responses to the use of teaching variations at 86%.